Design of a 5 GT Pilot Boat with a 700 HP Outboard Engine for Optimal Efficiency and Performance Suitable for Indonesian Waters - Sutrisno; Hadi Prasutiyon; Erik Sugianto; Muchlas Adi Sunjaya (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
The development of maritime technology drives innovation in ship design, including a 5 GT pilot boat designed for high efficiency and performance in Indonesian waters. This vessel is constructed using Fiberglass-Reinforced Plastic (FRP), a material known for its strength and cost-effectiveness compared to wood. Measuring 12.4 meters in length, the boat is powered by a total of 700 HP from two Yamaha F350UCB V8 5.3L F350 outboard engines, enabling it to reach an optimal speed of approximately 25 knots. Stability and power analysis, conducted using the Maxsurf application, indicate that positioning the engines at the stern on both the right and left sides provides the best stability with an inclination angle of 73.6°. This design is expected to enhance operational efficiency and support pilotage activities in dynamic waters.